Transforming Dispute Resolution in the Global Business Era: The Advantages of Arbitration in Realizing Legal Certainty, Efficiency, and Confidentiality of the Parties - Nadia Br pasaribu; Yuliastri Khorvica Harahap; Maisari Nasution; Putri Marganti Pasaribu; Tika Afrianti (ISNU Sumatera Utara, 2024)
The development of increasingly complex business relationships leads to an increase in the potential for disputes that require an effective, fast, and legal certainty resolution mechanism. Dispute resolution through litigation often faces various obstacles, such as lengthy processes, complex procedures, and limitations in maintaining the confidentiality of the parties. This research aims to analyze the advantages of arbitration as a modern dispute resolution mechanism in realizing efficiency, legal certainty, and protection of the interests of the parties. This research uses a normative legal research method with a qualitative approach through library research. Research data was obtained through a study of laws and regulations, legal literature, scientific journals, and legal documents related to arbitration. The results of the study show that arbitration has various advantages over litigation, namely procedural flexibility, time and cost efficiency, final and binding nature of the award, protection of confidentiality, and opportunities for parties to choose arbitrators with special expertise. Nevertheless, arbitration still faces challenges in the form of relatively high fees and limited oversight mechanisms for awards. In conclusion, arbitration is a relevant dispute resolution instrument in the modern legal system and needs to be strengthened in order to be able to provide effective, professional, and fair settlements.